MULTIFOCAL OSTEONECROSIS OF LARGE JOINTS AFTER COVID-19: CLINICAL AND IMAGING FEATURES - Valieva K. N.; Rustamova U. M.; Ismatullaeva M. N.; Valieva K. U. (Modern American Journals, 2025)
Osteonecrosis (ON) is a serious musculoskeletal complication that may occur after COVID-19 infection. It is associated both with vascular endothelial dysfunction and with corticosteroid therapy used for severe cases. There is limited knowledge regarding the characteristics of multifocal osteonecrosis (MFON) in post-COVID patients.
Keywords: Osteonecrosis; Multifocal osteonecrosis; COVID-19; MRI; Femoral head; Corticosteroids